Obstetric Determinants of Postpartum Complications among Mothers in Indonesia: Evidence from the 2023 Indonesian Health Survey - Meirica Rosaline Safitri; Asri C. Adisasmita (Indonesian Journal of Global Health Research, 2025)
Postpartum complications remain a significant contributor to maternal morbidity and mortality in Indonesia, yet national data on their determinants remain limited. Understanding the role of obstetric factors in postpartum outcomes is essential for informing maternal health strategies, particularly in low- and middle-income settings where delays in risk detection and care are common. This study aims to analyze the association between obstetric factors and the occurrence of postpartum complications using data from the 2023 Indonesian Health Survey (SKI). This cross-sectional analysis utilized secondary data from the 2023 Indonesian Health Survey (SKI), involving women aged 15–54 years who delivered in the last five years. The dependent variable was postpartum complications, while independent variables included parity, place of delivery, mode of delivery, type of birth attendant, and pregnancy-related conditions. Descriptive statistics, Chi-Square tests, and multivariate logistic regression were used in the analysis. The results showed that primiparous women, those who delivered via cesarean section, gave birth in hospitals, were attended by doctors, and experienced complications during pregnancy were significantly more likely to report postpartum complications. These findings underscore the need for improved antenatal risk screening, enhanced referral systems, and targeted maternal health interventions to prevent adverse outcomes in the postpartum period in Indonesia.